Extent and types of management consulting services to SMEs in Vojvodina - Dukić, Dragan; Majstorović, Aleksandar; Aničić, Jugoslav (Industrija, 2013)
Growth and development of small and medium enterprises depends on many external and internal factors, as well as the volume, type and quality of support available to them. This paper highlights the importance of management knowledge and skills in small business, and the importance of management consulting in their acquisition and development. We have researched and analyzed the extent to management consulting (MC) services, separately in the micro, small and medium enterprises. In addition, we learn which types of MC services are most commonly used by companies of different sizes. In that way, we provided qualitative and quantitative data for each group of enterprises, both in the type and volume of services used. It is observed that micro-enterprises use a small amount  MC services, and those of more general type. With the growth of the enterprises, comes an increase in scope, and sophistication of services used. The results may be useful both for small and medium enterprises, as well as for institutional and private providers of management consulting services.
Keywords: Service; Enterprise